Blockade of IL-1 family cytokines in the treatment of rheumatoid arthritis - Wang, Kexin; Luo, Haoge; Liu, Liping; Gao, Hang; Song, Yanyan; Li, Dong (Frontiers in Pharmacology, 2025)
Rheumatoid arthritis (RA), a chronic autoimmune disorder, imposes a substantial global health burden through elevated disability rates, systemic complications, and socioeconomic consequences. Chronic synovitis and progressive joint destruction characterize this disease, driven by dysregulated innate and adaptive immune responses that amplify synovial inflammation, osteoclastogenesis, and irreversible tissue damage. Aberrant activation of interleukin (IL) -1 family cytokines critically contributes to RA pathogenesis. These cytokines mediate dual mechanisms: pro-inflammatory agonists like IL-1β, IL-18, and IL-36 accelerate disease progression, whereas insufficient levels of anti-inflammatory antagonists such as IL-1Ra and IL-37 disrupt the balance required to suppress pathogenic cascades. Clinical trials evaluating IL-1-targeting biologics—including anakinra and canakinumab—have demonstrated robust early efficacy. However, late-stage interventions exhibit diminished therapeutic returns, largely due to irreversible joint damage and compensatory activation of redundant cytokine networks. These findings emphasize the need for precise patient stratification. Single-pathway IL-1 inhibition faces inherent limitations, driving the development of multi-target strategies to counteract cytokine redundancy and reduce therapeutic resistance. This review systematically analyzes the mechanistic roles of IL-1 family cytokines in RA, evaluates clinical outcomes and safety profiles of IL-1-targeted therapies, and proposes innovative strategies to advance RA treatment.